Cerebellar control of fear learning via the cerebellar nuclei–Multiple pathways, multiple mechanisms? - Urrutia Desmaison, Julie D.; Sala, Romain W.; Ayyaz, Ahsan; Nondhalee, Pimpimon; Popa, Daniela; Léna, Clément (Frontiers in Systems Neuroscience, 2023)
Fear learning is mediated by a large network of brain structures and the understanding of their roles and interactions is constantly progressing. There is a multitude of anatomical and behavioural evidence on the interconnection of the cerebellar nuclei to other structures in the fear network. Regarding the cerebellar nuclei, we focus on the coupling of the cerebellar fastigial nucleus to the fear network and the relation of the cerebellar dentate nucleus to the ventral tegmental area. Many of the fear network structures that receive direct projections from the cerebellar nuclei are playing a role in fear expression or in fear learning and fear extinction learning. We propose that the cerebellum, via its projections to the limbic system, acts as a modulator of fear learning and extinction learning, using prediction-error signaling and regulation of fear related thalamo-cortical oscillations.